The Pros and Cons of Life Without Parole - Appleton, Catherine (The British journal of criminology, 2007)
The question of how societies should respond to their most serious crimes if not with the death penalty is perhaps the oldest of all the issues raised by the two-century struggle in western civilization to end the death penalty' (Bedau, 1990: 481). In this article we draw attention to the rapid and extraordinary increase in the use of life imprisonment without parole' in the United States. We aim to critically assess the main arguments put forward by supporters of whole life imprisonment as a punishment provided by law to replace the death penalty and argue against life-long detention as the ultimate sanction